Socio-economics and livelihood status of coastal fishers in the Puducherry Union Territoryof India - An exploratory study - Kumaran, M.; Anand, P. R.; Vijayakumar, S.; Deboral Vimala, D.; Jayanthi, M.; Sairam, C. V.; Vijayan, K. K. (Indian Journal of Fisheries, 2021)
Knowledge on the socio-economics and livelihood status of fishers is important in view of stagnating capture fisheries production in recent years and to plan suitable additional livelihood interventions. A study undertaken among the coastal fishers (n=145) of Puducherry and Karaikal Districts of Puducherry Union Territory along the south-east coast of India in 2018-19, indicated that while fishing was the full time occupation for Karaikal fishers, about 56% of the coastal inland fishers of Puducherry District realised their income from non-fisheries occupations due to insufficient emolyment and income in fisheries. The fishers’ mean livelihood score was found to be 70% which indicated that they need supplementary activities for employment and income generation. Therefore, Department of Fisheries (DoF) may plan a two-pronged strategy comprising natural resource restoration measures such as re-stocking and stock enhancement involving habitat protection. Similarly the DoF may inititate capacity enhancement programme on culture based fisheries like cage and pen farming in the open waters with the technical support of research institutions and homestead based additional income generating activities with the support of non-governmental organisations to enhance the livelihood security of fishers. It is right time that the DoF may propose plans for both resource conservation and culture fisheries based livelihood security programmes under the newly launched Prime Minister’s Fisheries Development Scheme (Pradhan Mantri Matsya Sampada Yojana-PMMSY) of Govt. of India to ensure the livelihood security of fishers. Keywords: Cage and pen farming, Coastal fishers, Livelihood security, PMMSY, Stock enhancement